Language and Power: Analyzing Discourse and Communication Dynamics in Political and Social Contexts - Richa Fionasari; Eko Saputra (Penelitian dan Pengembangan Ilmu, 2024)
This research investigates the relationship between language and power in political and social contexts, with a focus on the construction of reality and public perception. Key concepts such as language, power, construction of reality, public perception, and the role of political and social actors are discussed in depth. The research method is based on a systematic literature review by collecting data from various relevant international databases. The results of the discussion reveal that language is not only a means of communication, but also an instrument of power used to influence public opinion and maintain dominance in society. The implications of this research highlight the importance of understanding the complex relationship between language, power, and politics in modern societies for the development of more effective and inclusive policies. This study provides a strong foundation for further research in understanding the dynamics of language and power in contemporary politics and society.